Innate immunity in stem cell-derived hepatocytes. (5th July 2018) - Fischer, Lena; Hay, David C.; O'Farrelly, Cliona
Abstract : Stem cell-derived hepatocyte-like cells (HLCs) offer great opportunities for studies of host–pathogen interactions and tissue regeneration, as well as hepatotoxicity. To reliably predict the outcome of infection or to enhance graft survival, a finely tuned innate immune system is essential. Hepatocytes have long been considered solely metabolic and their critical innate immune potential is only recently gaining attention. Viral infection studies show that pathogen detection by cytosolic receptors leads to interferon (IFN) induction in primary hepatocytes and HLCs. IFN expression in HLCs is characterized by strong expression of type III IFN and low expression of type I IFN which is also a characteristic of primary hepatocytes. The response to IFN differs in HLCs with lower interferon-stimulated gene (ISG)-expression levels than in primary hepatocytes. Tumour necrosis factor-alpha (TNF-α) signalling is less studied in HLCs, but appears to be functional. Expression of toll-like receptors (TLR) 2–5, 7 and 9 has been reported in primary hepatocytes but has been poorly studied in HLCs. In summary, although they retain some immature features, HLCs are in many ways superior to hepatoma cell lines for cell-based modelling. In this review, we will provide an overview of innate immune signalling in HLCs and how this compares with primary hepatocytes. This article is part of the themed issue 'Designer human tissue: coming to a lab near you'.